m+12=8m

Simple and best practice solution for m+12=8m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+12=8m equation:



m+12=8m
We move all terms to the left:
m+12-(8m)=0
We add all the numbers together, and all the variables
-7m+12=0
We move all terms containing m to the left, all other terms to the right
-7m=-12
m=-12/-7
m=1+5/7

See similar equations:

| g−62=14 | | n+30=28 | | r-6=2r | | V=3.14x18^2x8 | | 7.2y=18.3 | | 13x^2=90 | | (5x)+(2x)=90 | | -2a-5=3(5-2a) | | 3k+38=92 | | (60)+(4x)=90 | | 13–8x=141 | | 3(-2x+4)=-6x-12* | | 20=48t^2 | | 3s+4.75=21 | | 93/4−2s=21/4 | | x=74x≥13 | | 5=-1-7/k | | (4x+9)(5x+5)=180 | | 3(x+4)=-3* | | x^2-14x=287 | | 9x=135* | | 10(s-9)=-172 | | c/5c+5=30 | | x+4+x-5=90 | | -8x+8+3x-6=-3x+2 | | -8x+8+3x-6=-3x+2*4 | | -8-11x10=30 | | 7y+46=5(y+6) | | 2(3s+6)=60 | | -12x-15=-3(2x+3)* | | m+12=3m+4 | | -6(x-1)=-3-12 |

Equations solver categories